Evaluation of Functionality of P&TC and Availability of Hospital Formulary in various Hospitals of Lahore, Pakistan (International Journal of Pharmacy & Integrated Health Sciences, 2021)
Objectives: To evaluate the functionality of P&TC and availability of hospital formulary in different hospitals of Lahore, Pakistan.